2010
DOI: 10.1108/14777261011088656
|View full text |Cite
|
Sign up to set email alerts
|

Learning practice? Exploring the links between transitions and medical performance

Abstract: Transitions are explained in terms of the inseparability of learning, practice and performance and we introduce the concept of the transition as a critically intensive learning period to draw attention to this phenomenon. Also identified are implications for practice, research and regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 38 publications
(30 reference statements)
3
45
0
1
Order By: Relevance
“…For policy-makers and regulatory agencies, concern often centres upon ensuring quality and reliability of professional decision-making throughout transition periods (e.g. Kilminster et al 2010). Educators, on the other hand, tend to focus upon…”
Section: Structured Abstractmentioning
confidence: 99%
“…For policy-makers and regulatory agencies, concern often centres upon ensuring quality and reliability of professional decision-making throughout transition periods (e.g. Kilminster et al 2010). Educators, on the other hand, tend to focus upon…”
Section: Structured Abstractmentioning
confidence: 99%
“…The purpose of the original study from which this paper is drawn, Learning responsibility? Exploring doctors' transitions to new levels of medical performance, was to develop better understandings of these transitions and more details have been reported elsewhere (Kilminster et al, 2010(Kilminster et al, , 2011Zukas and Kilminster, 2012). Essentially we used a learning perspective to understand doctors' transitions.…”
Section: Methodsmentioning
confidence: 99%
“…Park, Woodrow, Reznick, Beales, and MacRae (2007) have identified patient care and education, as well as self-(imposed) and collegial relationships, as major responsibilities in the daily work of surgical resident doctors and faculty members, thus emphasizing their complex structure and collective character. From the perspective of junior physicians' performance at various levels of responsibility, Kilminster, Zukas, Quinton, and Roberts (2010) have argued that junior physicians' transitions through healthcare can be referred to as critical intense learning periods (CILPs), in which the role of the workplace and those with whom they work have a decisive impact. In our study, we found that relational tensions between the physicians' professional responsible doings illustrate the connections between learning and support of others' learning and that they can be seen as important features of CILPs.…”
Section: Discussionmentioning
confidence: 99%